Research progress of new coronavirus (COVID-19): Theoretical study - Moeed, Yahya Ali Gaber; Yue, Liu; Ling, Li Chung (Journal of medical and pharmaceutical sciences, 2020)
Objective: Provide a holistic perspective the new coronavirus (covid-19) to assist researchers and improving areas for future response plans to deal with these diseases, and to provide a summary of the factors that help stop their development.Methods: This is a theoretical study conducted through a comprehensive review of the literature and research in the research engines (PubMed), (Read) and (ELSEVIER) and other new studies published in Chinese.Results: Until now no effective drug for the treatment of new coronavirus pneumonia (covid-19) has been found. The development of vaccines is still in animal experiments. Recommendations and measures to control the spread of infection are still the only way to prevent the spread of covid-19 virus. However, some drugs have been proven effective. Effectively alleviates virus-associated infections (Covid-19) and also used certain factors during the SARS and MERS epidemics. For example, lopinavir (LPV) is an effective drug to inhibit protease activity of coronavirus. Significant progress has been made in diagnosis, as some studies have found that CT scans may show certain abnormalities in the chest even before symptoms appear.Discussion: The COVID-19 virus remains a global concern and more research is needed to control it. It needs to find all sources of infection, especially those that are still mysterious and still need to develop precautions, especially for hospitals staff and those who need direct contact with patients.
Keywords: COVID-19; prevention; treatment; diagnosis